Monte carlo simulations of chain dimensions and conformational properties of various poly(n-alkyl methacrylates) in solution - Karyappa, Rahul B.; Natarajan, Upendra (Journal of Macromolecular Science Part B-Physics, 2008)
Rotational Isomeric State (RIS) Metropolis Monte Carlo (RMMC) simulations of the conformational properties and chain dimensions of a series of chemically different poly(n-alkyl methacrylates) including poly(methyl methacrylate), poly(n-butyl methacrylate), poly(n-hexyl methacrylate), and poly(phenyl methacrylate), in the theta state were investigated, and (r(2)/M)(1/2), (s(2)/M)(1/2) and C(n) were calculated and compared in order to obtain fundamental understanding of the influence of the chemical structure. Simulations were conducted for different molecular weights. Results obtained from the simulations are compared with experimentally obtained dimensions in the literature using the Mark-Houwink relationship as well as, in some cases, data available from direct determinations in theta solvents. Good agreement between simulation and experimental data was obtained. The backbone conformation is predominantly trans in these polymers. Increase in bulkiness and rigidity of the substituting acrylate side group results in an increase in trans and a decrease in gauche backbone conformer population. In the case of rotatable bonds in the side-group structure, increase in rigidity of the side group leads to a decrease in the trans population, although this effect is not uniformly observed.
Keywords: chain dimensions; Monte Carlo simulation; polymethacrylate; theta solvent

Effect of composition on chain dimensions of styrene-methylmethacrylate random copolymers under theta condition - Karyappa, Rahul B.; Natarajan, Upendra (Journal of Macromolecular Science Part B-Physics, 2011)
Rotational-isomeric-state (RIS)-Metropolis Monte Carlo simulations are performed on poly(styrene-ran-methylmethacrylate) random copolymers to study the intrinsic unperturbed (theta-condition) dimensions. Mean-squared end-to-end distance (< r(2)>(o)), mean-squared radius of gyration (< s(2)>(o)), and characteristic ratio (C(n)) have been calculated for these copolymers constituted by different overall chemical compositions (styrene fractions 0.29, 0.56, and 0.70). Calculations were carried out with chains of 500 repeating units. With an increase in the styrene content there is an increase in (< r(2)>(o)), `, and C(n), in agreement with experimental observations. An increase in the fraction of trans conformational states in the backbone torsion angles is found to be responsible for the exhibited chain expansion behavior. The dimensions calculated by the Monte Carlo simulations agree well with experimental values reported in the literature.
Keywords: chain dimensions; Monte Carlo; poly(methyl methacrylate); Polystyrene; random copolymer; theta conditions

Molecular simulations of the conformational properties of atactic poly(2-ethylbutyl methacrylate) - Karyappa, Rahul B.; Natarajan, Upendra (Journal of Applied Polymer Science, 2012)
RIS Metropolis Monte Carlo (RMMC) simulations were used to determine the unperturbed theta-state chain dimensions of atactic stereoconfigurations of poly (2-ethylbutyl methacrylate) [PEBMA]. Root mean-squared end-to-end distance (< r(2)>(o)/M)(1/2) and characteristic ratio (Cn) were calculated along with the backbone torsion angle distribution. The simulated properties are in very good agreement with experimental results. The values of the PEBMA chain dimensions are in-between those corresponding ones for poly(n-butyl methacrylate) and poly (n-hexyl methacrylate) thereby showing the effect of branching in the side-chain. (c) 2012 Wiley Periodicals, Inc. J Appl Polym Sci, 2012
Keywords: chain dimensions; conformations; Monte Carlo simulation; poly(2-ethylbutyl methacrylate); vinyl polymer